The Effect of Quizizz as an Evaluation Tool on Student Learning Outcomes in Islamic Religious Education - Islami, Nelsi; Jumrodah, Jumrodah; Abdullah, Abdullah (Kamaya: Jurnal Ilmu Agama, 2025)
This study tries to find out how using Quizizz as a way to check learning affects students' results in the subject World and Hereafter Balance at MTsN 1 Kota Palangka Raya. The study uses an experimental approach with a design that only includes a post-test for comparison. Two classes were involved: class VIII-5 as the control group and class VIII-7 as the experimental group, making a total of 60 students. The method used to select the students was purposive sampling. The data was analyzed with SPSS version 26, using an Independent Samples t-test and also a quantitative descriptive analysis through percentages. The findings showed that students in the experimental group had better learning results than those in the control group. Most students from both groups gave positive comments about using Quizizz, which was considered “good. ” The t-test results also showed a big difference between the two groups, meaning that using Quizizz had a significant effect. So, it is hoped that teachers can use interactive tools like Quizizz in their lessons to help students learn better and stay more engaged. The study suggests that using digital tools like Quizizz can be a good way to evaluate learning, and teachers should consider using this technology to improve learning results, engagement, and interest in learning. The implications of this study indicate that the use of interactive digital media such as Quizizz can be an effective alternative in the learning evaluation process. It is hoped that teachers can integrate this technology to improve student learning outcomes, engagement, and motivation in learning.